Analysis of a Single Vertical Pendulum Mechanism on the Pontoon-Boat as a Wave Energy Harvester - Aida Annisa Amin Daman; Wiwiek Hendrowati; Harus Laksana Guntur (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2018)
The aims of this study are to model the wave energy harvester device using a single pendulum on a pontoon called Single Vertical Pendulum Mechanism (SVPM) and analyze the voltage generated by the mechanism. The simulation method was conducted in order to provide the power generated by SVPM. The SVPM’s dimension was designed on a laboratory scale and the wave amplitude was adjusted by the amplitude on the laboratory pool. The mechanism model uses wave energy as the excitation force of the pendulum. The pendulum oscillates and drives the transmission gear which transmits the force to the generator. The generator produces electrical energy. The variation used in the simulation was the mass of the pendulum, the length of the pendulum’s arm, and the wave amplitude. The maximum power that can be generated by SVPM was 5,735 Watt occurred when the arrangement of SVPM was using the pendulum mass of 0,75 kg and the pendulum length of 0,2 m. The parameter that most affect the generated power of SVPM was the wave amplitude.